Algorithmic Game Theory 4th International Symposium, SAGT 2011, Amalfi, Italy, October 17-19, 2011. Proceedings - Persiano, Giuseppe; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the Fourth International Symposium on Algorithmic Game Theory, SAGT 2011, held in Amalfi, Italy, in October 2011. The 26 revised full papers presented together with 2 invited lectures were carefully reviewed and selected from 65 submissions. The papers are organized in topical sections on auctions and advertising, quality of solutions, externalities, mechanism design, complexity, network games, pricing, as well as routing games.
Keywords: Computer science; Electronic data processing; Computer simulation; Computer Science; Simulation and Modeling; e-Commerce/e-business.; Models and Principles; Computers and Society; Numeric Computing; Probability and Statistics in Computer Science